HYBRID LEARNING MODEL IN MA’HAD ‘ALY UIN MAULANA MALIK IBRAHIM MALANG - Taufiqurrochman, R.; Prasetiyo, Agung; Amrullah, Hasyim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research identifies and implements a multimedia-based Hybrid Learning Model at Ma'had Aly UIN Malang, integrated with the university system. Utilizing a qualitative case study approach with thematic analysis, it explores factors influencing the model. Supporting factors encompass leadership policies, component synergy, adequate facilities, and tech-savvy Generation Z students. Inhibiting factors include the Covid-19 pandemic, limited media, suboptimal communication, and underutilized human resources. Despite challenges, the Hybrid Learning Model accelerates the transformation of Ma'hadi education, serving as a transformative role model. Implementation of the Hybrid Learning Model at Ma'had Aly UIN Malang involves various strategies such as Project-Based Learning, Problem-Based Learning, and Blended Learning, along with strict adherence to health protocols. Supporting factors such as leadership policies and students' tech proficiency, along with inhibiting factors such as the Covid-19 pandemic and media limitations, play crucial roles in this process. The effects of implementing this Hybrid Learning Model include the development of new learning strategies, enhanced facility provision, mastery of digital technology, preparation for integrated self-learning, and support for the transformation of Ma'hadi education as a model for change.